The transcription factor c-Myb regulates CD8+T cell stemness and antitumor immunity - Gautam, Sanjivan; Fioravanti, Jessica; Zhu, Wei; Le Gall, John B.; Brohawn, Philip; Lacey, Neal E.; Hu, Jinhui; Hocker, James D.; Hawk, Nga Voong; Kapoor, Veena; Telford, William G.; Gurusamy, Devikala; et al. (Nature Immunology, 2019)
Stem cells are maintained by transcriptional programs that promote self-renewal and repress differentiation. Here, we found that the transcription factor c-Myb was essential for generating and maintaining stem cells in the CD8 + T cell memory compartment. Following viral infection, CD8 + T cells lacking Myb underwent terminal differentiation and generated fewer stem cell–like central memory cells than did Myb-sufficient T cells. c-Myb acted both as a transcriptional activator of Tcf7 (which encodes the transcription factor Tcf1) to enhance memory development and as a repressor of Zeb2 (which encodes the transcription factor Zeb2) to hinder effector differentiation. Domain-mutagenesis experiments revealed that the transactivation domain of c-Myb was necessary for restraining differentiation, whereas its negative regulatory domain was critical for cell survival. Myb overexpression enhanced CD8 + T cell memory formation, polyfunctionality and recall responses that promoted curative antitumor immunity after adoptive transfer. These findings identify c-Myb as a pivotal regulator of CD8 + T cell stemness and highlight its therapeutic potential.
CRIS-Team Scopus Importer:2023-03-23